MENINGKATKAN KEMAMPUAN PRA-MATEMATIKA DENGAN MENGGUNAKAN MEDIA BALOK CUISENAIRE PADA ANAK KELOMPOK A2 PAUD HAQIQI KOTA BENGKULU - Maya Lasuka; M. Nasirun; Mona Ardina (Jurnal Ilmiah POTENSIA, 2018)
This study aied to improve the pre-mathematics ability through the introduction to pattern activity and classification  by using Cuisenaire block media on children of group A2 at Early Childhood Education Program (PAUD) of Haqiqi of Bengkulu City. The research method used in this study was Classroom Action Research (CAR) which was conducted through two cycles and each cycle consisted on three meetings. The subject of the study were as many as 9 students consisted of 5 male student and 4 female students. Data collection technique was done by using observation method. Data analysis was conducted by calculating the average score and learning mastery score. The result of the study revealed that there was improvement on pre-mathematic ability of the children through the introduction to pattern activity and classification with the average  score of 4,3  and learning mastery of 86% categorized as very good criteria. It is suggested for the next research to use cuisenaire block as a media to measure other abilities with several aspect that need to be considered such as size and basic pattern.